Spatiotemporal, metabolic, and therapeutic characterization of altered functional connectivity in major depressive disorder. Issue 5 (17th January 2018) - Sheng, Jintao; Shen, Yuedi; Qin, Yanhua; Zhang, Lei; Jiang, Binjia; Li, Yaoyao; Xu, Luoyi; Chen, Wei; Wang, Jinhui
Abstract: Although imbalanced functional integration has been increasingly reported in major depressive disorder (MDD), there still lacks a general framework to characterize common characteristic and origin shared by the integrative disturbances. Here we examined spatial selectivity, temporal uniqueness, metabolic basis, and therapeutic response of altered functional connectivity (FC) in MDD by analyzing both cross‐sectional and longitudinal multimodal functional magnetic resonance imaging data from 35 patients and 34 demographically matched healthy controls. First, based on a voxel‐wise, data‐driven, graph‐based degree centrality approach, the bilateral anterior cingulate gyri, middle frontal gyri and superior frontal gyri, and the right parahippocampal gyrus were robustly identified to show decreased FC in MDD. Further spatiotemporal analyses revealed that these regions exhibited hub‐like features and were selectively located in limbic and default mode networks spatially and, relative to other areas in the brain, exhibited unique, frequency‐dependent oscillation power (stronger within 0.01–0.027 Hz and weaker within 0.027–0.073 Hz) and less dynamical variability of whole‐brain FC profiles temporally. Moreover, a cross‐modality fusion analysis showed that all MDD‐related FC impairments were associated with reduced cerebral blood flow (CBF); however, there existed multiple regions that showed reduced CBF but had intact FC in the patients, which resulted in a decreased FC‐CBF coupling and implied an earlier emergence of reduced CBF than impaired FC in MDD. Finally, the disrupted FC in MDD gradually recovered over the course of drug treatment (2 and 12 weeks). Altogether, these findings could help establish a general framework to provide mechanistic insights into integrative dysfunctions in MDD.